Earnings management, capital management and signaling: European evidence - Wäck, Pekka (My University, 2016)
Prior research has shown that banks use loan loss provisions (LLPs) for earnings management, capital management and signaling. The purpose of this paper is threefold. First, it aims to investigate the relationship between loan loss provisions and earnings management of European Union (EU) banks. Second, this paper examines whether bank management uses LLPs to signal positive private information about future profits to investors. Lastly, it examines whether banks use LLPs as a tool to manage regulatory capital. Additionally, this paper examines how the 2007 financial crisis has affected bank managers’ discretionary behavior over LLPs and whether listed banks utilize LLPs differently relative to unlisted banks. The sample includes commercial banks annual financial statement data gathered from the period 2005 to 2012. The sample consists of observations for listed and unlisted banks from 28 different EU countries. A single-stage regression model is used to model the non-discretionary component of LLPs and examine the relationship between it and capital, earnings management and signaling. The results demonstrate that EU banks do engage in earnings management and do not use LLPs for capital management during the sample period. Both findings are in accordance with prior studies. As expected, European Union banks engage in less earnings management after the financial crisis. Additionally, listed commercial banks seem to engage in less earnings management relative to unlisted banks. Contrary to prior studies, this paper finds no evidence of signaling in the European banking industry.
Keywords: Earnings management; capital management; loan loss provisions; signaling; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|